University teachers’ beliefs about the use of generative artificial intelligence for teaching and learning - Beatriz Cabellos; Beatriz Cabellos; Carlos de Aldama; Juan-Ignacio Pozo (Frontiers in Psychology)
IntroductionThe growing presence of generative artificial intelligence (GenAI) in our society, particularly in the educational field, is undeniable. This fact has led to various studies on its implications for learning and teaching. However, as with other technological resources, these implications will depend on how teachers use GenAI. Therefore, it is essential to identify teachers’ beliefs regarding the use of GenAI for teaching and learning.MethodsTo this end, a questionnaire was designed and completed by 321 university teachers. This questionnaire consisted of two parts. The first included questions about the participants’ demographic information and a Likert scale on teachers’ pedagogical beliefs. The second part consisted of a 32-item Likert scale that evaluated teachers’ beliefs about the impact of GenAI on their students’ learning and their own teaching. These aspects were reflected through items that considered GenAI as either an educational opportunity or a threat.ResultsThe results showed that, of all the variables analyzed, only pedagogical beliefs and the frequency of previous GenAI use influenced beliefs about GenAI usage. Specifically, teachers with constructivist beliefs saw greater potential in GenAI compared to others. Similarly, teachers who regularly used these technologies had more positive beliefs about their educational use than those who used them sporadically or not at all. Lastly, it was also observed that while teachers valued the positive effects of GenAI on their teaching work, they also considered that its use could be detrimental to the learning processes of their students, making them more superficial.DiscussionThese findings underline the importance of providing teachers with training focused on constructive approaches that enable them to maximize the potential of GenAI in education. In particular, it is crucial to promote teaching practices that, through student-centered GenAI use, foster active and reflective processes in students, aligned with the competencies demanded by today’s society.